2009
DOI: 10.1128/jcm.00627-09
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Bacteremia and Osteomyelitis Resulting in Fatal Bacteremic Pneumonia with Multiorgan Failure Caused by Mycobacterium simiae in a Non-Human Immunodeficiency Virus-Infected Adult

Abstract: Bacteremic pneumonia caused by Mycobacterium simiae in non-human immunodeficiency virus (HIV)-infected patients has rarely been reported. We describe a non-HIV-infected adult with refractory bacteremia, osteomyelitis, and colonization of M. simiae in the respiratory tract who subsequently developed fatal bacteremic pneumonia. The isolate was confirmed as M. simiae by 16S rRNA gene analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…In future, a large-scale prospective cohort study is required to explore the incidence rate of NTM infections. Similar to a previous study (20), productive cough, dyspnea, malaise, fever, sweat, and body weight loss were the most common signs and symptoms of M. simiae infection among the Iranian patients. However, the most frequent imaging finding was nodular lesions (100z) in Iranian patients, which makes our study distinct from those in a previous study (8).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In future, a large-scale prospective cohort study is required to explore the incidence rate of NTM infections. Similar to a previous study (20), productive cough, dyspnea, malaise, fever, sweat, and body weight loss were the most common signs and symptoms of M. simiae infection among the Iranian patients. However, the most frequent imaging finding was nodular lesions (100z) in Iranian patients, which makes our study distinct from those in a previous study (8).…”
Section: Discussionsupporting
confidence: 86%
“…Previously, this organism was presumed to cause disseminated infections only in immunocompromised individuals only. However, recent reports have confirmed that M. simiae can also disseminate in immunocompetent patients (10,(19)(20)(21). The rate of NTM infections varies geographically worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…M. simiae is a slow growing mycobacterium which is resistant to conventional antituberculous drugs [ 6 ]. Since this microorganism is commonly found in the environment, it has been implicated in pseudo outbreaks [ 9 ] as well as nosocomial infections [ [7] , [8] ]. Most cases of M. simiae reported among apparently immunocompetent individuals involve pulmonary disease, and only rarely involve dissemination or manifest with bone involvement [ [7] , [8] ].…”
Section: Discussionmentioning
confidence: 99%
“…Although NTM form an integral part of the environment, they have potential to cause clinical disease in immunocompromised hosts [ [2] , [3] , [4] ]. M. simiae most commonly causes pulmonary disease, however, bone and genitourinary system involvement has also been described with disseminated disease occurring in the immunocompromised hosts, especially patients with HIV infection and a CD4 count <50 cells/mm 3 [ [5] , [6] , [7] , [8] ]. Herein we describe a case of vertebral M .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent reports showed that disseminated M. simiae can also be seen in immunocompetent patients [10]. M. simiae may rarely be a cause hematogenous spread from pneumonia, leading to multifocal osteomyelitis in immunocompetent patient [15].…”
Section: Clinical Manifestationmentioning
confidence: 99%